Missing Children: Incidences and Characteristics of Runaway Children and Resources Available to Them - Stacy Daniels; Mark A. Brennan (EDIS, 2006)
FCS-2254, a 5-page fact sheet by Stacy Daniels and M.A. Brennan, is the first in a two-part series focusing on missing children. This paper takes a close look at runaways: who they are, the scope of the problem, and what professionals can do to help. It also considers the related problem of throwaways: children who have been abandoned or forced to leave their homes. Includes resource list and references. Published by the UF Department of Family Youth and Community Sciences, October 2006.